Nursing of a patient with functional constipation treated by Traditional Chinese Medicine holographic scraping (中医全息刮痧治疗功能性便秘1例的护理) - JIA Zongyi (贾宗祎); HU Hairong (胡海荣); TANG Ling (唐玲) (中西医结合护理)
This paper reported the Traditional Chinese Medicine (TCM) holographic scraping therapy and related nursing management for a patient with functional constipation. Based on the theory of TCM external treatment, holographic meridians scraping was carried out, and corresponding measures such as psychological nursing, health education, lifestyle and exercise guidance were adopted to relieve the symptoms of the patient with functional constipation. (本文报告中医全息刮痧治疗1例功能性便秘患者的效果, 总结相关护理经验。通过开展中医外治疗法即全息刮痧, 配合心理护理、健康教育、生活指导、运动指导等综合护理干预, 有效改善患者便秘症状。)